Instantaneous pressure–flow velocity relations of systemic venous return in patients with univentricular circulation. Issue 3 (1st September 1999) - Kaulitz, R; Bergman, P; Luhmer, I; Paul, T; Hausdorf, G
Abstract : OBJECTIVE: To assess the pressure and flow velocity relations and respiratory variability of the systemic venous and hepatic venous return in patients with univentricular circulation. PATIENTS: 15 selected patients who had undergone cavopulmonary anastomosis (10) or atriopulmonary anastomosis (5). Mean age at operation was 55.1 months (range 9 to 145). Studies were done at 75.5 (32.6) months (mean (SD)) after the operation. SETTING: Tertiary referral centre. METHODS: Patients were studied using simultaneous recordings of ECG, pressure trace, respirometer trace, and pulsed Doppler echocardiography. Mean systemic venous pressure and pulmonary vascular resistance did not differ significantly between the two patient groups. RESULTS: After total cavopulmonary anastomosis, systemic venous pressure tracings showed a flattened pressure curve without any dependence on cardiac or respiratory cycle. After atriopulmonary anastomosis, right atrial pressure tracings showed a significantly higher "a" wave corresponding to atrial contraction, without any respiratory variability. Pulsed Doppler examination of the superior and inferior caval vein and hepatic vein after total cavopulmonary anastomosis did not show a reverse flow after atrial contraction. The inspiratory to expiratory velocity ratio of antegrade flow revealed a significant dependence of flow on changes in intrathoracic pressure in the intra-atrial tunnel, caval veins, and hepatic vein. During expiration, decrease or cessation of antegrade hepatic venous flow was documented. After an atriopulmonary anastomosis, there was a biphasic antegrade venous flow pattern without significant respiratory variation. CONCLUSIONS: After total cavopulmonary anastomosis, there was marked respiratory dependence of systemic and hepatic venous return, whereas after an atriopulmonary anastomosis venous flow pattern varied according to cardiac cycle and pressure trace. The effects of total cavopulmonary anastomosis on venous return might counteract its other haemodynamic advantages.